Human isoprenoid synthase enzymes as therapeutic targets - Park, Jaeok; Matralis, Alexios N.; Berghuis, Albert M.; Tsantrizos, Youla S. (Frontiers in Chemistry, 2014)
The complex biochemical network known as the mevalonate pathway is responsible for the biosynthesis of all isoprenoids in the human body, which consists of a vast array of metabolites that are vital for proper cellular functions. Two key isoprenoids, farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP) are responsible for the post-translational prenylation of small GTP-binding proteins, and serve as the biosynthetic precursors to numerous other biomolecules. The down-stream metabolite of FPP and GGPP is squalene, the precursor to steroids, bile acids, lipoproteins and vitamin D. In the past, interest in prenyl synthase inhibitors focused mainly on the role of the FPP in lytic bone diseases. More recently, pre-clinical and clinical studies have strongly implicated high levels of protein prenylation in a plethora of human diseases, including non-skeletal cancers, the progression of neurodegenerative diseases and cardiovascular diseases. In this review, we focus mainly on the potential therapeutic value of down-regulating the biosynthesis of FPP, GGPP and squalene. We summarize the most recent drug discovery efforts and the structural data available that support the current on-going studies.